Perhitungan Dan Perencanaan Struktur Gedung Kantor BPBD Kabupaten Kampar - Beny Setiawan (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
The Kampar Regency Regional Disaster Management Agency (BPBD) was formed based on Kampar Regency Regional Regulation No. 7 of 2010 concerning the Regional Disaster Management Agency. The BPBD Office is currently located in the Old Regent's Office Complex since 2015, and is planning to add another floor to the office building. The addition of the (new) floor is intended for office space and meeting rooms, while the (old) lower floor remains in its original function. The condition of the old building's structure has structural columns of 30x40 cm2 and beams measuring 25x30 cm2 with the quality of the concrete, the quality of the reinforcing steel, the size and quantity are also unknown. The planning method for this new floor uses SNI 1726-2019 for structural planning procedures, SNI 2052-2017 for steel reinforcement standards and SNI 1727-2020 for minimum loading standards on buildings. This study uses structural analysis software that is commonly used as a tool for calculating structural planning. The results of this study, the old structure cannot support the floor of the new structure in accordance with the planned function, but the old structure can be strengthened by adding new reinforcing steel with fy= 400 MPa, while the quality of concrete (f'c) K-300 reinforcement or 25 MPa. Reinforcement design for columns using 12D20 with stirrups Ø10-150 and design for beam reinforcement 6D19 (top) 4D19 (bottom) with stirrups Ø10-100 on abutments, 4D19 (top), 6D19 (bottom) with stirrups Ø10-150 in the field.